Development of online facility management system for FTMSK computer center / Husni Ahmad Hanafi - Ahmad Hanafi, Husni (Faculty of Computer and Mathematical Sciences, 2007)
This Online Facility Management System is basically the system that is built to manage the equipment in Faculty of Information Technology & Quantitative Science Computer Center. This system allow user to make booking of the equipment online. Before this, students and lectures need to go to the Computer Center to book. But, by using this system user can make booking from anywhere and anytime. The target users for this system are students and lectures of FTMSK. Only students and lectures of FTMSK are allowed to use this system because it required user UiTM identification. For student, there can choose to make booking of computer accessories or laptop. But for lecturer there is additional option for them to choose, software. User also can use to check whether the equipment they want to book available or not. For administrator, they can use this system to update the equipment and accessories for booking and can accept and reject the booking through this system. This system hopefully can help FTMSK Computer Center management become more effiision.